The Relationship Between Picky Eater and The Nutrional Status of Preschool Children at Gotong Royong Kindergarden in Surabaya, Indonesia - Pangastutik, Deby Artika; Fatmaningrum, Widati; Al Farizi, Sofia (Journal of Community Medicine and Public Health Research, 2024)
One of the eating behavior disorders in preschool children is picky eater, a behavior that is picky about food so that children experience limited consumption of a variety of foods. This impacts the nutritional status of children, which can affect their health. Therefore, this study aims to determine the relationship between children's eating behavior disorders (picky eaters) and the nutritional status of preschool children at Kindergarten Gotong Royong Surabaya, Indonesia. This was an observational analytical research with a cross-sectional research design. The sampling method used purposive sampling technique. Data were collected by filling out the CEBQ (Child Eating Behavior Questionnaire) questionnaire and anthropometric measurements of body weight and height, as well as measuring nutritional status using the indicators BB/TB (0-6 months) and BMI/U (>60 months). All data were processed using IBM SPSS v25.0 software with the Spearman rank correlation test. The results of the study showed that 53.6% of preschool children at KB-TK Gotong Royong Surabaya had eating behavior disorders (picky eaters), 46.4% of the children were non-picky eaters, 41.0% had poor nutritional status, and 43.6% had normal nutrition who were mostly non-picky eaters. The bivariate analysis results of the correlation test obtained a p-value of 0.001 (α>0.05). These data showed a relationship between picky eating disorders and the nutritional status of preschool children at Kindergarten Gotong Royong Surabaya.